Determinants of modern contraceptive use: A cross-sectional study among market women in the Ashiaman Municipality of Ghana. (2020) - Asiedu, Agnes; Asare, Bernard Yeboah-Asiamah; Dwumfour-Asare, Bismark; Baafi, Diana; Adam, Abdul-Razak; Aryee, Sawdah Esaka; Ganle, John Kuumuori
Abstract: Background: In Ghana, the use of modern contraceptives has been shown to be consistently low among women in informal jobs. This study examined the awareness, knowledge and availability of modern contraceptives, prevalence and determinants of modern contraceptive use among market women in the Ashiaman Municipality of Ghana. Method: A cross-sectional study was conducted among 290 market women of the reproductive age. Data were collected between May and July 2017 using a structured questionnaire. Pearson chi-square and Fischer exact tests, and logistic regression analysis were conducted to examine the determinants of modern contraceptives use. Results: The average age of respondents was 29 ± 5.96 years. There was a universal awareness and high knowledge (98.6%) about modern contraceptives; however the prevalence of their usage was 36.9%. Determinants of modern contraceptive use included negative thoughts about the use of contraceptives (p = 0.020), and husbands/partners deciding the use of contraceptive (p = 0.004). Multiple regression showed lower odds of modern contraceptive use among respondents that had negative thoughts about modern contraceptives use (OR = 0.39; 95% CI = 0.21–0.75) compared to those with positive thoughts about modern contraceptive use; and respondents whose husbands or partners decided for them to use contraceptives (OR = 0.34; 95% CI = 0.18–0.63) compared to women whose husbands or partners did not decide for them to use contraceptive. Conclusion: The key determinants identified underline the need for interventions that emphasize practical education of both men and women focusing on the benefits of modern contraceptive services to help demystify the misconceptions and negative thoughts about modern contraceptives, and decrease male's disapproval of their use.